The other side of dawn - Marsden, John, 1950- (Marsden, John, 1950- Tomorrow series, 2002)
Ellie and her friends, five Australian teenagers who survived the enemy invasion of their country, use guerrilla tactics to support a major counterattack by New Zealand troops.